Dynamics of Smart Systems and Structures: Concepts and Applications - Lopes, Vicente [UNESP]; Steffen, Valder; Savi, Marcelo Amorim (Springer Nature, 2016)
Written by a team of experts that has been working together for several years in the context of a research network involving international institutions, this book brings several applications related to smart material systems such as vibration and noise control, structural health monitoring, energy harvesting and shape memory alloys. Furthermore, this book also provides basic knowledge on the fundamentals of smart material systems and structures. Consequently, the present title serves as an important resource for advanced undergraduate and graduate students. In addition, it serves as a guide for engineers and scientists working with smart structures and materials both with an application and basic research perspective. Smart material systems and structures represent a new paradigm which is increasing the capabilities of engineering systems. Adaptability and versatility are some important aspects related to such systems. In brief, research on smart materials is characterized by synergistically combining different physical features, such as mechanical, electrical, chemical, and magnetic. As a result, smart material technologies have a huge potential to enhance the performance of engineering structures opening unlimited opportunities to innovation and economic benefits.